Aspiration and Evaluation of Gastric Residuals in the Neonatal Intensive Care Unit. Issue 1 (January 2015) - Parker, Leslie; Torrazza, Roberto Murgas; Li, Yuefeng; Talaga, Elizabeth; Shuster, Jonathan; Neu, Josef
<x xml:space="preserve">Abstract</x> The routine aspiration of gastric residuals (GR) is considered standard care for critically ill infants in the neonatal intensive care unit (NICU). Unfortunately, scant information exists regarding the risks and benefits associated with this common procedure. This article provides the state of the science regarding what is known about the routine aspiration and evaluation of GRs in the NICU focusing on the following issues: (1) the use of GRs for verification of feeding tube placement, (2) GRs as an indicator of gastric contents, (3) GRs as an indicator of feeding intolerance or necrotizing enterocolitis, (4) the association between GR volume and ventilator-associated pneumonia, (5) whether GRs should be discarded or refed, (6) the definition of an abnormal GR, and (7) the potential risks associated with aspiration and evaluation of GRs. Recommendations for further research and practice guidelines are also provided.